Sustainability of Microfinance Institutions in Financial Crisis - Lenka Dokulilová; Karel Janda; Pavel Zetek (European Financial and Accounting Journal, 2009)
The aim of this paper is to clarify the problems of microfinance and the sustainability of microfinance institutions (MFI) in financial crisis. We find, that MFIs are often considered as one of the most effective and flexible strategies in the fight against global poverty. Due to several often unsolvable problems obstructing the easier and faster development of these institutions such as: ethnical problems, managerial resources, legal recourses, unfortunate recourses and other, the operations of MFIs are often not sufficiently efficient. The microfinance sector is in general known for its adaptability and quite healthy survival of past financial crises. However, current global financial crisis is testing the resilience of MFIs hardly. The MFIs are much more connected to international financial markets now than it was the case during previous crises. Therefore we expect that they will not survive the crisis without bearing some loses. But the expected losses are relatively smaller when compared to other financial institutions.
Keywords: G01; G21; 650; Financial crisis; Microfinance; Microcredit; MFIs